Antitumor components and mechanisms of Zanthoxylum bungeanum Maxim with medicine and food homology - Du, Yuhua; Duan, Shuai; Yang, Yi; Tibenda, Joanna Japhet; Huang, Shicong; Nan, Yi; Zhang, Zhe; Yuan, Ling (Frontiers in Pharmacology, 2025)
Zanthoxylum bungeanum Maxim (Z. bungeanum) is a medicinal and edible plant commonly used to improve the flavor of Chinese cuisine due to its unique numbing taste. It is recognized for its medicinal properties, including bodywarming, relieving cold, promoting blood circulation, and alleviating pain. Additionally, Z. bungeanum has been extensively studied for its antitumor properties. In this study, various scientific databases and network pharmacology were used to search for information about Z. bungeanum and its components for the treatment of tumors. Numerous active components of Z. bungeanum have been identified, demonstrating antitumor properties. We discovered that Z. bungeanum can modulate multiple signaling pathways across various targets using network pharmacological predictions, highlighting its strong antitumor potential. The components of Z. bungeanum and the traditional Chinese medicine compound containing Z. bungeanum can promote apoptosis, arrest the cell cycle, inhibit cell invasion and metastasis, promote autophagy, and increase the sensitivity of chemotherapeutic drugs through P53, PI3K/AKT, Wnt/β-catenin and other signaling pathways, which are effective against various cancers, including hepatocellular cancer, gastric cancer, and breast cancer. Z. bungeanum and its extracts have demonstrated promising effects against various tumors, indicating their potential use in future cancer therapies and offering new strategies for tumor treatment. However, clinical studies evaluating the antitumor efficacy and toxicity of Z. bungeanum in humans are scarce. Therefore, well-designed clinical trials should be prioritized in the future to establish a solid foundation for its use in cancer treatment.